Kikuchi Fujimoto disease associated with cryptogenic organizing pneumonia: case report and literature review - Hua Feng (BMC Infectious Diseases, 2010)
Abstract Background The association of Kikuchi Fujimoto disease (KFD) with cryptogenic organizing pneumonia (COP) is extremely rare. We report a case of simultaneous diagnosis of KFD and COP. Case Presentation A 33-year-old male presented with a 1-month cough illness and fever lasting for 5 days. The chest radiograph revealed double lower lobe infiltrate, which was unresponsive to antibiotics. A cervical lymph node was first found in the development of this disease. Bronchoscopy, bronchoalveolar lavage and lung biopsy established the diagnosis of COP, while a lymph node biopsy was consistent with KFD. The patient improved on steroids. Conclusions KFD and COP are possible part of a disease continuum, rather than separate entities.